Modelling of Digital Radar - Jonasson Svärdsby, Albin (My University, 2016)
The advances in modern electronics pave way for new ways to design radar systems. The existence of Analogue to Digital Converters (ADC) capable of sampling at GHz make it possible to sample the RF signal directly, removing the need for prior down mixing. This gives a possibility to design very simple receiver channels and move traditional operations from hardware to software. This greatly helps cutting cost of manufacturing and development and opens up for a very configurable system. This configurability comes at the cost of decreased selectivity, resulting in that external signals outside the radar system's signal bandwidth but inside the receiver band will become amplified as well, with the risk of saturating the amplifiers. Because of this it is interesting to study the impact of the non-linearities on detectability. The simple design of the system makes it feasible to simulate the full system chain from transmitter to signal processing after the receiver. This thesis treats the methods used to create a model in order to simulate the operation and non-linear effects of a Uniform Linear Array (ULA) digital pulse doppler radar system from generation of transmission waveform to the signal processing of the sampled output from the receiver channels. The methods involve electronic simulations of amplifiers utilising a 5th degree polynomial and filtering and sampling processes. The thesis further features techniques used to enhance the Signal to Noise Ratio (SNR) of a desired signal from a phased array and position it in a 3D space with 2 room dimensions and 1 velocity dimension. The model is then utilised to study the effects of non-linear effects of the system when the input to the receiver is disturbed by a strong clutter signal or a strong external signal. The thesis also treats the effect on detectability of a target when an external signal give rise to higher order harmonics from amplifier saturation and clipping during sampling that then is folded into the radar system's final sampling band. The thesis finds it feasible to perform full system simulations from waveform generation to detection and it is found that the non-linear effects due to strong disturbances negatively affect the desired target SNR and may in some cases be the source of false detections. The results is found by studying common radar cases, with varying input power to the receiver. The thesis finds that it is possible to digitally suppress external signals outside the final sampling band but the decrease in SNR for the desired signal, due to saturation of the radar system, still remains.
Keywords: Informations- och kommunikationsteknik; Elektroteknik och elektronik; Signalbehandling; Information & Communication Technology; Electrical Engineering, Electronic Engineering, Information Engineering; Signal Processing